Hemagglutinin-specific CD4+ T-cell responses following 2009-pH1N1 inactivated split-vaccine inoculation in humans. Issue 42 (9th October 2017) - Tan, Shuguang; Zhang, Shihong; Wu, Bin; Zhao, Yingze; Zhang, Wei; Han, Min; Wu, Ying; Shi, Guoli; Liu, Yingxia; Yan, Jinghua; Wu, Guizhen; Wang, Hua; et al.
Highlights: Humoral and cellular immune responses against an inactivated 2009 pandemic H1N1 vaccine. Hemagglutinin-specific CD4 + T cells could be primed after vaccine inoculation. Hemagglutinin-specific T-cell responses declined to baseline 6 weeks after vaccination. Virus-specific CD8 + T cells were not elevated throughout vaccination. Abstract: Influenza A virus remains a major threat to public health, and the inactivated split-virus vaccine is the most prevalent vaccine used worldwide. However, our knowledge about cellular immune responses to the inactivated influenza virus vaccine and its correlation with humoral responses are yet limited, which has restricted our understanding of the vaccine's protective mechanisms. Herein, in two clinical trials, T-cell responses specific for both previously identified human leucocyte antigen (HLA)-I-restricted epitopes from influenza virus and hemagglutinin (HA) protein were longitudinally investigated before, during, and after a two-dose vaccination with the inactivated 2009 pandemic H1N1 (2009-pH1N1) vaccine. A robust antibody response in all of the donors after vaccination was observed. Though no CD8 + T-cell responses to known epitopes were detected, HA-specific T-cell responses were primed following vaccination, and the responses were found to be mainly CD4 + T-cell dependent. However, HA-specific T-cells circulating in peripheral blood dropped to baseline levels 6 weeks after vaccination, but humoral immune responses maintained a high level for 4 months post-vaccination. Significant correlations between the magnitude of the HA-specific T-cell responses and hemagglutination inhibition antibody titers were demonstrated, indicating a priming role of HA-specific T-cells for humoral immune responses. In conclusion, our study indicates that HA-specific CD4 + T-cell responses can be primed by the inactivated 2009-pH1N1 vaccine, which may coordinate with the elicitation of antibody protection. These findings would benefit a better understanding of the immune protective mechanisms of the widely used inactivated 2009-pH1N1 vaccine.